Buildings and Streets / photographs of varied streets in Spanish Town, St. Catherine - Georgian Society of Jamaica (St. Catherine, Jamaica : Georgian Society of Jamaica, 1970)
Photographs showcasing the architectural design and styles of a variety of buildings in Jamaica's old capital, Spanish Town in the parish of St. Catherine.
level 1
These photographs are also digitzed.
No restriction
Keywords: Georgian Society Collection; Spanish Town Street, St. Catherine, Jamaica; Photographs